Housing First for People with Severe Mental Illness Who are Homeless: A Review of the Research and Findings from the at Home—Chez soi Demonstration Project. (November 2015) - Aubry, Tim; Nelson, Geoffrey; Tsemberis, Sam
Objective: To provide a review of the extant research literature on Housing First (HF) for people with severe mental illness (SMI) who are homeless and to describe the findings of the recently completed At Home (AH)–Chez soi (CS) demonstration project. HF represents a paradigm shift in the delivery of community mental health services, whereby people with SMI who are homeless are supported through assertive community treatment or intensive case management to move into regular housing. Method: The AH–CS demonstration project entailed a randomized controlled trial conducted in 5 Canadian cities between 2009 and 2013. Mixed methods were used to examine the implementation of HF programs and participant outcomes, comparing 1158 people receiving HF to 990 people receiving standard care. Results: Initial research conducted in the United States shows HF to be a promising approach, yielding superior outcomes in helping people to rapidly exit homelessness and establish stable housing. Findings from the AH–CS demonstration project reveal that HF can be successfully adapted to different contexts and for different populations without losing its fidelity. People receiving HF achieved superior housing outcomes and showed more rapid improvements in community functioning and quality of life than those receiving treatment as usual. Conclusions: Knowledge translation efforts have been undertaken to disseminate the positive findings and lessons learned from the AH–CS project and to scale up the HF approach across Canada.